Simulasi dan Analisis Desain Mold Dengan Software Autodesk Fusion 360 Untuk Produk Aksesoris - Tri Wahyu Ridono; Adhes Gamayel; Mohamad Zaenudin (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2024)
The manufacturing process is still being developed. The injection molding process is a manufacturing process that is often used in the production of plastic products. Using software with predetermined parameters, injection mold simulation of a predetermined product is carried out on the carabiner design. The parameters used are then assessed with quality prediction based on the best simulation results. If there is a product that does not meet the quality prediction value given (i.e. the value is less than optimal), improvements are made by changing the injection mold design or mold design. Three runner layout designs were made in such a way as to assess which of the runner layout designs for the carabiner mold had the highest quality prediction value. Then, from each runner layout design, variations in gate diameter sizes of 2 mm, 4 mm and 6 mm were made. Based on the simulation results that have been carried out, the best runner and gate layout is obtained in Design 1 with a gate diameter of 4 mm, whose quality prediction value reaches 100%. Then, the lowest quality prediction was obtained in Design 1 with a gate diameter of 6 mm.